Household Portfolio Choice, Reference Dependence, and the Marriage Market - Wenchao Li; Changcheng Song; Shu Xu; Junjian Yi (Institute of Labor Economics (IZA), 2017)
This paper bridges the financial market and the marriage market using a reference-dependent mechanism. Male-biased sex ratios induce families with sons to hold more risky assets, since competitive marital payment in a tight market raises the reference level of marriage expenditure for such families. Using the 2013 China Household Finance Survey data, we find that a 0.1 increase in the sex ratio raises the probability of participating in the stock market by 25.7 percent, or the stock share of liquid wealth by 42.7 percent for families with a son; there appears no effect for families with a daughter.
Keywords: D03; G02; G11; 330; household portfolio choice; reference dependence; prospect theory; sex-ratio imbalance; difference-in-differences estimate